2006
DOI: 10.1021/pr060124w
|View full text |Cite
|
Sign up to set email alerts
|

Statistically Integrated Metabonomic−Proteomic Studies on a Human Prostate Cancer Xenograft Model in Mice

Abstract: A novel statistically integrated proteometabonomic method has been developed and applied to a human tumor xenograft mouse model of prostate cancer. Parallel 2D-DIGE proteomic and 1H NMR metabolic profile data were collected on blood plasma from mice implanted with a prostate cancer (PC-3) xenograft and from matched control animals. To interpret the xenograft-induced differences in plasma profiles, multivariate statistical algorithms including orthogonal projection to latent structure (OPLS) were applied to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(96 citation statements)
references
References 45 publications
0
96
0
Order By: Relevance
“…Statistical evaluation and interpretation were performed separately and provided an insight into the underlying biochemistry. Rantalainen et al 89 demonstrated a novel approach using the OPLS method to integrate 2D-DIGE proteomic and NMR metabolic data from a human tumor xenograft mouse model of prostate cancer.…”
Section: Multi-"omics" Studiesmentioning
confidence: 99%
“…Statistical evaluation and interpretation were performed separately and provided an insight into the underlying biochemistry. Rantalainen et al 89 demonstrated a novel approach using the OPLS method to integrate 2D-DIGE proteomic and NMR metabolic data from a human tumor xenograft mouse model of prostate cancer.…”
Section: Multi-"omics" Studiesmentioning
confidence: 99%
“…This integration of multiple 'omics' data has been initially performed in small-scale animal studies integrating metabolic profiles with quantitative trait locus data in a diabetic rat model (Dumas et al 2007) and in combined metabolic and proteomic data of a mouse model of prostate cancer (Rantalainen et al 2006). With the availability of increasingly powerful high-throughput technologies, computational tools and integrated knowledge bases, multiple 'omics' integration is now being applied to large-scale human clinical and population studies.…”
Section: Metabolomics and Other Omics For Individualised Trt In Menmentioning
confidence: 99%
“…The common reference sample also serves the purpose of facilitating the spot matching between gels by having the same sample on all gels. Since its inception, the DIGE method has been used to quantify protein changes between distinct biological groups including cancer cells [13][14][15]. Several studies on statistical aspects of the DIGE technique have been published as well [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%